2015
DOI: 10.3762/bjoc.11.153
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the synthesis of α-aminoalkylidenebisphosphonates and their asymmetric phosphonyl-phosphinyl and phosphonyl-phosphinoyl analogues

Abstract: SummaryA convenient approach has been developed to α-aminoalkylidenebisphosphonates and their asymmetric phosphonyl-phosphinyl and phosphonyl-phosphinoyl analogues by α-phosphonylation, α-phosphinylation or α-phosphinoylation of 1-(N-acylamino)alkylphosphonates, that, in turn, are easily accessible from N-acyl-α-amino acids. Effective electrophilic activation of the α-position of 1-(N-acetylamino)alkylphosphonates was achieved by electrochemical α-methoxylation of these compounds in methanol, mediated with NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The pyrenyl thioamidoalkylphosphonates formed in this reaction can be readily transformed into the corresponding fluorescent amidoalkylphosphonates. It is worthy to note that this class of compounds offers numerous possibilities of chemical transformations [ 35 36 ]. The pyrenyl amidoalkylphosphonates emit fluorescence with quantum yields ca.…”
Section: Discussionmentioning
confidence: 99%
“…The pyrenyl thioamidoalkylphosphonates formed in this reaction can be readily transformed into the corresponding fluorescent amidoalkylphosphonates. It is worthy to note that this class of compounds offers numerous possibilities of chemical transformations [ 35 36 ]. The pyrenyl amidoalkylphosphonates emit fluorescence with quantum yields ca.…”
Section: Discussionmentioning
confidence: 99%
“…The electrophilicity of the α-carbon atom of the synthesized α-ethoxyphosphonate derivative 3 is too low to allow its direct transformation into the target bisphosphonate 5 using the Michaelis–Arbuzov-type reaction with triethyl phosphite [ 30 ]. Therefore, to increase the electrophilicity of this position, it was necessary to convert α-ethoxyphosphonate 3 to the corresponding phosphonium salt 4 , which is much more reactive and thus susceptible to subsequent reaction with the nucleophilic triethyl phosphite.…”
Section: Resultsmentioning
confidence: 99%
“…Other substrates that have been used in this reaction in the presence of Hünig’s base and methyltriphenylphosphonium iodide as catalysts are diethyl 1-( N -acetylamino)-1-triphenylphosphoniumalkylphosphonate tetrafluoroborates 4 , which can be considered as α-functionalized triphenylphosphonium derivatives of 1-( N -acylamino)alkylphosphonates [ 30 ]. The starting phosphonium salts 4 were synthesized here from diethyl 1-aminoalkylphosphonates readily available from N -acyl-α-amino acids [ 31 , 32 ] by initially subjecting them to electrochemical oxidation to introduce the nucleofugal methoxy group into the α-position, which was followed by nucleophilic substitution of the obtained diethyl 1-( N -acetylamino)-1-methoxyalkylphosphonates with triphenylphosphonium tetrafluoroborate ( Scheme 1 , pathway a).…”
Section: Introductionmentioning
confidence: 99%
“…Further research on phosphorus analogs of α-amino acids 37 revealed the possibility of transforming them into bisphosphoric acid esters 43 , which also exhibit important biological activity ( Scheme 13 ) [ 56 , 57 ].…”
Section: 1-aminoalkyltriarylphosphonium Derivativesmentioning
confidence: 99%